Customer Satisfaction In The Digitalisation Era: Evidence Of South Africa Banking Sector (Journal of Namibian Studies : History Politics Culture, 2024)
By investigating the effects of digitalisation as a service quality dimension on customer satisfaction, customer retention, and competitive advantage—all of which are critical for the success of customer service—this study hopes to add to the body of knowledge in the South African banking industry. Relationship hypotheses were investigated empirically. To find out if there is a statistically significant relationship between the variables being examined, regression analysis was used. The results of the empirical study demonstrated a statistically significant positive correlation between digitization of banking services and customer satisfaction with respect to customer experience and customer satisfaction with regard to digital banking convenience. In order to maintain the relevance of retail banks in an uncertain environment, this study concludes with sage advice that may help managers and banking professionals enhance certain areas of their customer service based on the relationships identified.